Wpływ zmian zyskowności na oczekiwane stopy zwrotu z akcji spółek - weryfikacja podejścia A. Damodarana dotyczącego kalkulacji współczynnika beta księgowego na podstawie danych giełdowych - Słoński, Tomasz; Płachciak, Ewelina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
A market risk exposure measurement with accounting data is an important subject for each private enterprise. According to A. Damodaran, the volatility of net income could be a good approximation of market risk exposure. In this paper, the Damodaran approach was verified on the sample of four Warsaw Stock Exchange subindices. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 379-387